2014
DOI: 10.1177/0734282914550383
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Self-Efficacy Scale

Abstract: Emotional self-efficacy (ESE) is an important aspect of emotional functioning, with current measures for children and adolescents focused on the measurement of self-beliefs in relation to the management of emotions. In the present study, we report the psychometric properties of the first adaptation of the Emotional Self-Efficacy Scale for youth (Youth-ESES) that measures additional aspects of ESE, such as perceiving and understanding emotions and helping others modulate their emotions. Participants were 192 yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 43 publications
2
9
0
2
Order By: Relevance
“…The TEIQue-CF measures a complex blend of perceived emotional competencies (e.g., emotion expression), facets of emotional personality (e.g., affective disposition) and self-beliefs (e.g., motivation) (Mavroveli et al, 2008). The newly developed Emotional Self-Efficacy Scale (ESE; Qualter et al, 2015a) offers a “cleaner” examination of discrete perceived emotional competencies in children, and as a next step it would be desirable for researchers to validate and extend the current findings using this tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TEIQue-CF measures a complex blend of perceived emotional competencies (e.g., emotion expression), facets of emotional personality (e.g., affective disposition) and self-beliefs (e.g., motivation) (Mavroveli et al, 2008). The newly developed Emotional Self-Efficacy Scale (ESE; Qualter et al, 2015a) offers a “cleaner” examination of discrete perceived emotional competencies in children, and as a next step it would be desirable for researchers to validate and extend the current findings using this tool.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers may also consider refining the tools used to capture those relationships. Specifically, the use of an age-appropriate TEI measure that accommodates sub-facet analysis (e.g., ESE: Qualter et al, 2015a) would allow more fine-grained examination of how competency beliefs about specific emotion skills (e.g., confidence in regulating one’s own emotions/the emotions of others etc.) impact wellbeing across time.…”
Section: Discussionmentioning
confidence: 99%
“…According to these ideas, some measures of ESE have been prepared for children [13] and adolescents [8]. Using the modified adult version of ESE, Dacre Pool and Qualter measured ESE in adolescents [16]. This research supports the four sub-scales of ESES for adolescents, which are largely independent of cognitive ability.…”
Section: Introductionmentioning
confidence: 73%
“…The reliability and validity of the 27item adolescents ESES have been investigated. By implementing this scale for 192 11 to 13 years old adolescents at the state school of England, Qualter et al (2015) reported the Cronbach's alpha of 0.87 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Diversos autores sostienen que la percepción que tienen las personas acerca de su propia eficacia es una variable fundamental en la competencia humana debido a que influye en las estrategias, la motivación y la persistencia relacionadas al logro de un objetivo. Del mismo modo, repercute en la respuesta emocional ante situaciones complejas Álvarez et al, 2014;Prieto, 2001;Borzone Valdebenito, 2017;Flores León et al, 2010;Qualter et al, 2015;Rivera Heredia et al, 2016). Adicionalmente, la AE se relaciona con diversos fenómenos mentales y sociales, destacándose su efecto modulador en los procesos cognitivos, emocionales y conductuales.…”
Section: Validation De L'échelle D'auto-efficacité Pour Faire Face Auunclassified